Role of LGR5-positive mesenchymal cells in craniofacial development - Olbertová, Kristýna; Hrčkulák, Dušan; Kříž, Vítězslav; Jesionek, Wojciech; Kubovčiak, Jan; Ešner, Milan; Kořínek, Vladimír; Buchtová, Marcela (Frontiers in Cell and Developmental Biology, 2022)
Leucine-rich repeat containing G-protein-coupled receptor 5 (LGR5), a Wnt pathway member, has been previously recognised as a stem cell marker in numerous epithelial tissues.In this study, we used Lgr5-EGFP-CreERT2 mice to analyse the distribution of LGR5-positive cells during craniofacial development. LGR5 expressing cells were primarily located in the mesenchyme adjacent to the craniofacial epithelial structures undergoing folding, such as the nasopharyngeal duct, lingual groove, and vomeronasal organ. To follow the fate of LGR5-positive cells, we performed lineage tracing using an inducible Cre knock-in allele-in combination with Rosa26-tdTomato reporter mice. The slight expansion of LGR5-positive cells was found around the vomeronasal organ, in the nasal cavity, and around the epithelium in the lingual groove. However, most LGR5 expressing cells remained in their original location, possibly supporting their signalling function for adjacent epithelium rather than exerting their role as progenitor cells for the craniofacial structures. Moreover, Lgr5 knockout mice displayed distinct defects in LGR5-positive areas, especially in the reduction of the nasopharyngeal duct, the alteration of the palatal shelves shape, abnormal epithelial folding in the lingual groove area, and the disruption of salivary gland development. The latter defect manifested as an atypical number and localisation of the glandular ducts. The gene expression of several Wnt pathway members (Rspo1-3, Axin2) was altered in Lgr5-deficient animals. However, the difference was not found in sorted EGFP-positive cells obtained from Lgr5+/+ and Lgr5-/- animals. Expression profiling of LGR5-positive cells revealed the expression of several markers of mesenchymal cells, antagonists, as well as agonists, of Wnt signalling, and molecules associated with the basal membrane. Therefore, LGR5-positive cells in the craniofacial area represent a very specific population of mesenchymal cells adjacent to the epithelium undergoing folding or groove formation. Our results indicate a possible novel role of LGR5 in the regulation of morphogenetic processes during the formation of complex epithelial structures in the craniofacial areas, a role which is not related to the stem cell properties of LGR5-positive cells as was previously defined for various epithelial tissues.